Input Factor Analysis of Aedes Aegypti Controlling in Port Health Ofï¬ ce Class II Semarang Territory - Ridwan Rahmadi (JURNAL KESEHATAN LINGKUNGAN, 2017)
Dengue disease incidence in the Village Tanjungmas, District of Semarang Utara, Semarang City which is the working area of the Port Health Ofï¬ ce of class II Semarang is always high in the year 2013-2015. Port Health Ofï¬ ce is a unit Ministry of Health which has the main task of the disease and vector control such as Aedes aegypti. The factors that determine the activities to control the mosquito Aedes aegypti is the factor inputs consisting of man, money, method, machine, material, market, technology, time, information. This study aimed to analyze the input factor in the control of Aedes aegypti. This study was observational. The research variables were Aedes aegypti control input factors. Samples of respondents were implementing the activities taken by total population is composed of ofï¬ cers from the Port Health Ofï¬ ce Class II Semarang and cadres of larva monitoring. Data were analyzed descriptively. The results showed that the mans, money, machines, materials, times, the market and technology activities are in Class II Health Ofï¬ ce of Semarang accordance with the rules and standard operating procedures (SOP) Port Health Ofï¬ ce. While the method is not adjusted regulatory activities and SOP are larva survey by visual way. Therefore it is suggested that the method uses a single larva surveys to determine the type of mosquito larvae.